The state, identity politics and ethnic boundaries in Afghanistan: The case of Sunni Hazaras. Issue 2 (27th February 2023) - Ibrahimi, Niamatullah
Abstract: In recent years, a growing number of activists in Afghanistan have been proactively self‐identifying as Sunni Hazaras. The trend demonstrates an important shift that illuminates how ethnic boundaries may change and evolve in response to elite politics and state policies in Afghanistan. Many of the communities that are the subjects of new collective identity discourses share important commonalities, including shared belief in a common origin, with the Shi'a Hazaras. However, because the Shi'a Hazaras were persecuted and marginalised under successive regimes in Afghanistan, it was not common for these communities to publicly identify as Hazaras. Instead, they tended to identify with local identity categories such as those based on places of origin or as Tajiks because, like most Tajiks, they speak Dari and practise Sunni Islam. This article contributes to understanding these dynamics through a detailed examination of the National Council of the Sunni Hazaras of Afghanistan. Taking a social constructivist approach, it develops an argument that emphasises an interactive process between state formation and top‐down programmes of national identity construction and bottom‐up resistance by groups that appropriate and articulate ethnic and other forms of ethnic identities to demand political representation and symbolic recognition.